Effects of butyric acid and resistant starch supplementation on gut microbiota, fermentation and growth in weanling pigs fed propionic acid-preserved grain - Kathryn Ruth Connolly; Torres Sweeney; Vivian Gath; Stafford Vigors; John V. O’Doherty (Animal Feed Science and Technology, 2026)

The role of propionic acid as a feed additive and grain preservative on weanling pig performance and digestive health - Kathryn Ruth Connolly; Torres Sweeney; Dillon Padraig Kiernan; Alex Round; Marion T. Ryan; Vivian Gath; Shane Maher; Stafford Vigors; John V. O’Doherty (Animal Feed Science and Technology, 2025)

Environmental and ecological factors associated with stinging jellyfish at a tourism hotspot in the Gulf of Thailand - Rahul Mehrotra; Pasicha Chaikaew; Elouise Haskin; Kirsty Magson; Chad M. Scott; Ruth Doherty (Estuarine, Coastal and Shelf Science, 2024)

Organic acid preservation of cereal grains improves grain quality, growth performance, and intestinal health of post-weaned pigs - Shane Maher; Torres Sweeney; Dillon P. Kiernan; Marion T. Ryan; Vivian Gath; Stafford Vigors; Kathryn Ruth Connolly; John V. O’Doherty (Animal Feed Science and Technology, 2024)

Integrating Shared Socioeconomic Pathway-informed adaptation into temperature-related mortality projections under climate change - Kai Wan; Shakoor Hajat; Ruth M. Doherty; Zhiqiang Feng (Environmental Research, 2024)

Pharmacological inhibition of MERTK induces in vivo retinal degeneration: a multimodal imaging ocular safety assessment - Gregory Hamm; Gareth Maglennon; Beth Williamson; Ruth Macdonald; Ann Doherty; Stewart Jones; Jayne Harris; James Blades; Alexander R. Harmer; Peter Barton; Philip B. Rawlins; Paul Smith; et al. (Archives of Toxicology, 2022)
The receptor tyrosine kinase, MERTK, plays an essential role in homeostasis of the retina via efferocytosis of shed outer nuclear segments of photoreceptors. The Royal College of Surgeons rat model of retinal degeneration has been linked to loss-of-function of MERTK, and together with the MERTK knock-out mouse, phenocopy retinitis pigmentosa in humans with MERTK mutations. Given recent efforts and interest in MERTK as a potential immuno-oncology target, development of a strategy to assess ocular safety at an early pre-clinical stage is critical. We have applied a state-of-the-art, multi-modal imaging platform to assess the in vivo effects of pharmacological inhibition of MERTK in mice. This involved the application of mass spectrometry imaging (MSI) to characterize the ocular spatial distribution of our highly selective MERTK inhibitor; AZ14145845, together with histopathology and transmission electron microscopy to characterize pathological and ultra-structural change in response to MERTK inhibition. In addition, we assessed the utility of a human retinal in vitro cell model to identify perturbation of phagocytosis post MERTK inhibition. We identified high localized total compound concentrations in the retinal pigment epithelium (RPE) and retinal lesions following 28 days of treatment with AZ14145845. These lesions were present in 4 of 8 treated animals, and were characterized by a thinning of the outer nuclear layer, loss of photoreceptors (PR) and accumulation of photoreceptor outer segments at the interface of the RPE and PRs. Furthermore, the lesions were very similar to that shown in the RCS rat and MERTK knock-out mouse, suggesting a MERTK-induced mechanism of PR cell death. This was further supported by the observation of reduced phagocytosis in the human retinal cell model following treatment with AZ14145845. Our study provides a viable, translational strategy to investigate the pre-clinical toxicity of MERTK inhibitors but is equally transferrable to novel chemotypes.

Physical activity in relation to circulating hormone concentrations in 117,100 men in UK Biobank - Eleanor L. Watts; Aurora Perez-Cornago; Aiden Doherty; Naomi E. Allen; Georgina K. Fensom; Sandar Tin Tin; Timothy J. Key; Ruth C. Travis (Cancer Causes & Control, 2021)
Purpose Physical activity may reduce the risk of some types of cancer in men. Biological mechanisms may involve changes in hormone concentrations; however, this relationship is not well established. Therefore, we aimed to investigate the associations of physical activity with circulating insulin-like growth factor-I (IGF-I), sex hormone-binding globulin (SHBG, which modifies sex hormone activity), and total and free testosterone concentrations, and the extent these associations might be mediated by body mass index (BMI). Methods Circulating concentrations of these hormones and anthropometric measurements and self-reported physical activity data were available for 117,100 healthy male UK Biobank participants at recruitment. Objectively measured accelerometer physical activity levels were also collected on average 5.7 years after recruitment in 28,000 men. Geometric means of hormone concentrations were estimated using multivariable-adjusted analysis of variance, with and without adjustment for BMI. Results The associations between physical activity and hormones were modest and similar for objectively measured (accelerometer) and self-reported physical activity. Compared to men with the lowest objectively measured physical activity, men with high physical activity levels had 14% and 8% higher concentrations of SHBG and total testosterone, respectively, and these differences were attenuated to 6% and 3% following adjustment for BMI. Conclusion Our results suggest that the associations of physical activity with the hormones investigated are, at most, modest; and following adjustment for BMI, the small associations with SHBG and total testosterone were largely attenuated. Therefore, it is unlikely that changes in these circulating hormones explain the associations of physical activity with risk of cancer either independently or via BMI.

Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Lucy C. M. Omeyer; Philip D. Doherty; Sarah Dolman; Robert Enever; Allan Reese; Nicholas Tregenza; Ruth Williams; Brendan J. Godley (Frontiers in Marine Science, 2020)

Implications of future climate and atmospheric CO 2 content for regional biogeochemistry, biogeography and ecosystem services across East Africa - RUTH M. DOHERTY; STEPHEN SITCH; BENJAMIN SMITH; SIMON L. LEWIS; PHILIP K. THORNTON (Global Change Biology, 2010)
We model future changes in land biogeochemistry and biogeography across East Africa. East Africa is one of few tropical regions where general circulation model (GCM) future climate projections exhibit a robust response of strong future warming and general annual‐mean rainfall increases. Eighteen future climate projections from nine GCMs participating in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment were used as input to the LPJ dynamic global vegetation model (DGVM), which predicted vegetation patterns and carbon storage in agreement with satellite observations and forest inventory data under the present‐day climate. All simulations showed future increases in tropical woody vegetation over the region at the expense of grasslands. Regional increases in net primary productivity (NPP) (18–36%) and total carbon storage (3–13%) by 2080–2099 compared with the present‐day were common to all simulations. Despite decreases in soil carbon after 2050, seven out of nine simulations continued to show an annual net land carbon sink in the final decades of the 21st century because vegetation biomass continued to increase. The seasonal cycles of rainfall and soil moisture show future increases in wet season rainfall across the GCMs with generally little change in dry season rainfall. Based on the simulated present‐day climate and its future trends, the GCMs can be grouped into four broad categories. Overall, our model results suggest that East Africa, a populous and economically poor region, is likely to experience some ecosystem service benefits through increased precipitation, river runoff and fresh water availability. Resulting enhancements in NPP may lead to improved crop yields in some areas. Our results stand in partial contradiction to other studies that suggest possible negative consequences for agriculture, biodiversity and other ecosystem services caused by temperature increases.

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Spatial Scale Effects of Climate Scenarios on Simulated Cotton Production in the Southeastern U.S.A. - Ruth M. Doherty; Linda O. Mearns; K. Raja Reddy; Mary W. Downton; Larry McDaniel (Climatic Change, 2003)

A gridded reconstruction of land and ocean precipitation for the extended tropics from 1974 to 1994 - Ruth M. Doherty; Mike Hulme; Colin G. Jones (International Journal of Climatology, 1999)